Online journalism : the essential guide - Hill, Steve, ....-; Lashmar, Paul, ....- (Los Angeles : Sage Publications, 2014)
Online and social media have become indispensible tools for journalists, but you still have to know how to find and tell a great story. To be a journalist today, you must have not only the practical skills to work with new technologies, but also the understanding of how and why journalism has changed. Combining theory and practice, Online Journalism: The Essential Guide will take you through the classic skills of investigating, writing and reporting as you master the new environments of mobile, on-demand, social, participatory and entrepreneurial journalism. You will also develop must-have skills in app development for smartphones and tablets, as well as techniques in podcast, blog and news website production.
Keywords: Journalistiek en internet